Effect of Length and Up Ward Tapping on Physiology and Latex Yield on Rubber Plants RRIM 921 - Purwaningrum, Yayuk; Asbur, Yenni; Kusbiantoro, Dedi; Khairunisyah (Talenta Publisher, 2021)
RRIM 921 is a slow starter clone where the metabolic rate is low to moderate which has specific characteristics such as responsiveness to stimulants, relatively more resistance to exploitation pressure and generally thick recovered skin so that it is potential to be exploited. The aim of the study was to determine the effect of the length and direction of the top tapping on the physiology and production of rubber plant clones RRIM 921. This research was conducted at PT. Perkebunan Nusantara III (Persero) Kebun Sei Putih, Afd I is located in Galang District, Deli Serdang Regency, North Sumatra Province with an altitude of 25 meters above sea level with Ultisol soil type. Using a non-factorial Randomized Block Design (RAK) with three replications, as the treatment of groove length and upward tapping direction (S) consisted of 3 levels, namely S/2U d3 ETG/27d; S/4U d3 ETG/27d and S/8U d3 ETG/27d. The results showed that the S/8 U d3 ETG/27d treatment had the highest sucrose content of 3.97 mM, the highest latex Pi level was found in the S/4U d3 ETG/27d treatment of 26.01 mM and the highest Thiol content was found in the S/8U d3 ETG/ treatment. 27d by 1.03 mM. The highest latex production was in January on the S/4U d3 ETG/27d treatment of 13.98 g/p/s and the lowest in April on the S/8U d3 ETG/27d treatment of 0.85 g/p/s.